2004
DOI: 10.1523/jneurosci.4977-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Responses to Fearful and Happy Facial Expressions under Conditions of Binocular Suppression

Abstract: The human amygdala plays a crucial role in processing affective information conveyed by sensory stimuli. Facial expressions of fear and anger, which both signal potential threat to an observer, result in significant increases in amygdala activity, even when the faces are unattended or presented briefly and masked. It has been suggested that afferent signals from the retina travel to the amygdala via separate cortical and subcortical pathways, with the subcortical pathway underlying unconscious processing. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
243
3
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(275 citation statements)
references
References 42 publications
(67 reference statements)
21
243
3
2
Order By: Relevance
“…Enhanced activity in this subcortical pathway has been repeatedly reported during nonconscious perception of static facial and whole-body expressions of fear and joy in blindsight patients (20,25,27) as well as in healthy subjects in whom nonconscious perception was induced by experimental manipulations such as visual masking (19,21,23), binocular rivalry (33,34), or flash suppression (35). Consistent with these data, recent anatomical studies revealed the existence of direct anatomical connections between the SC, Pulv, and Amg in nonhuman primates (36), and in vivo tractography found the same connections in healthy human subjects and in patient GY (37).…”
Section: Discussionmentioning
confidence: 84%
“…Enhanced activity in this subcortical pathway has been repeatedly reported during nonconscious perception of static facial and whole-body expressions of fear and joy in blindsight patients (20,25,27) as well as in healthy subjects in whom nonconscious perception was induced by experimental manipulations such as visual masking (19,21,23), binocular rivalry (33,34), or flash suppression (35). Consistent with these data, recent anatomical studies revealed the existence of direct anatomical connections between the SC, Pulv, and Amg in nonhuman primates (36), and in vivo tractography found the same connections in healthy human subjects and in patient GY (37).…”
Section: Discussionmentioning
confidence: 84%
“…Other lesion studies have reported amygdala responsivity towards fearful or fear conditioned faces when presented in subjects' blind field (Morris et al, 2001) and during visual extinction (Vuilleumier et al, 2002). Neuroimaging studies have found similar results in amygdala activity using psychophysical techniques that manipulate subjects' awareness, including visual masking (Whalen, 1998;Whalen et al, 2004;Williams et al, 2006, but see Pessoa et al, 2006Phillips et al, 2004), and binocular rivalry (Pasley et al, 2004;Williams et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…Images of emotional faces rendered invisible through masking, can influence behavioural performance (Yang et al 2007;Faivre et al 2012;Almeida et al 2013) and produce brain activation in neuroimaging experiments linked to emotional processing, like enhanced amygdala responses to fearful faces (Williams et al 2004;de Gelder et al 2005). This suggests that the neural mechanisms required for detecting emotional expressions operate even when we are not aware of the stimulus.…”
Section: Unconscious Perceptual Organisationmentioning
confidence: 99%